Effective Peer Leader Attributes for the Promotion of Walking in Older Adults. - Kritz, Marlene; Thøgersen-Ntoumani, Cecilie; Mullan, Barbara; McVeigh, Joanne; Ntoumanis, Nikos (2020)
BACKGROUND AND OBJECTIVES: Peer-led interventions are promising for the promotion of physical activity behavior in older adults. However, little is known about the attributes of effective older peer leaders in such intervention programs. The objective was to determine what older adults perceive to be effective peer leader attributes. RESEARCH DESIGN AND METHODS: A mixed-methods concurrent triangulation design was used. Participants, aged 60 years and older, were recruited from retirement villages and existing walking groups in Western Australia. They were predominantly white, Australian-born, female, healthy retirees. The sample consisted of four groups of older adults: those who had taken part in past peer-led walking programs (experienced walkers; n = 18), those interested in joining as walkers in a peer-led walking intervention (inexperienced walkers; n = 43), those interested to take on a peer leader role (inexperienced peer leaders; n = 25), and those who had already served as peer leaders (experienced peer leaders; n = 15). Questionnaires measured perceived effective leadership attributes, and physical activity was measured using ActivPAL devices (N = 101; Mage [SD] = 75.36 [7.59]). Semistructured interviews were conducted with the majority of participants (N = 68; Mage [SD] = 74.68 [7.78]). RESULTS: Overall, participants described an effective peer leader as optimistic, compassionate, and friendly, but differences in perceptions were apparent between the groups. DISCUSSION AND IMPLICATIONS: Our findings advance knowledge about important characteristics of an effective older peer leader, which can inform peer leader training, recruitment of peer leaders, and future scale development.